Investigation of ultrasonic chronic total occlusion system on a rabbit model - Kasimzade, Ferit; Ada, Fatih; Karataş, Özhan (Journal of Surgery and Medicine, 2021)
Background/Aim: Advanced treatment options are needed in chronic total occlusion (CTO), which is a special subgroup of peripheral artery disease. Endothelial damage remains a problem in the endovascular treatment of peripheral artery CTO. In our study, this subgroup was examined with an ultrasonic total occlusion system for vascular endothelial damage on an animal model. Methods: We used twenty-four rabbits divided equally into three groups, created chronic total occlusion in the common iliac artery by applying a bioabsorbable polymer sponge, and waited four weeks for CTO formation. After four weeks, the samples obtained from the groups were examined histologically. Results: Significantly less endothelial damage was detected in the ultrasonic total occlusion system group compared to the directional atherectomy group (P<0.05). Conclusion: Ultrasonic atherectomy minimizes thrombus load and causes minimal endothelial damage. These findings show that the ultrasonic atherectomy method can be successfully used in CTO treatment.